Wafer‐Scale Fabrication of Suspended Single‐Walled Carbon Nanotube Arrays by Silver Liquid Dynamics. Issue 40 (21st August 2017) - Zhang, Jian; Liu, Siyu; Nshimiyimana, Jean Pierre; Deng, Ya; Hou, Gu; Chi, Xiannian; Hu, Xiao; Zhang, Zongzhi; Wu, Pei; Wang, Gongtang; Chu, Weiguo; Sun, Lianfeng
Abstract: Suspended single‐walled carbon nanotubes (SWNTs) have advantages in mechanical resonators and highly sensitive sensors. Large‐scale fabrication of suspended SWNTs array devices and uniformity among SWNTs devices remain a great challenge. This study demonstrates an effective, fast, and wafer‐scale technique to fabricate suspended SWNT arrays, which is based on a dynamic motion of silver liquid to suspend and align the SWNTs between the prefabricated palladium electrodes in high temperature annealing treatment. Suspended, strained, and aligned SWNTs are synthesized on a 2 × 2 cm 2 substrate with an average density of 10 tubes per micrometer. Under the optimal conditions, almost all SWNTs become suspended. A promising formation model of suspended SWNTs is established. The Kelvin four‐terminal resistance measurement shows that these SWNT array devices have extreme low contact resistance. Meanwhile, the suspended SWNT array field effect transistors are fabricated by selective etching of metallic SWNTs using electrical breakdown. This method of large‐scale fabrication of suspended architectures pushes the study of nanoscale materials into a new stage related to the electrical physics and industrial applications. Abstract : An effective, fast, and wafer‐scale fabrication of suspended single‐walled carbon nanotube (SWNT) arrays is demonstrated. Based on the dynamic motion of silver liquid in annealing process, the single‐walled carbon nanotubes in random orientations can be suspended, strained, and aligned. Under the optimal conditions, almost all SWNTs become suspended, suggesting great potential applications.